1994
DOI: 10.4049/jimmunol.152.8.3980
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of antibody-secreting cells induced in mucosal lymphoid tissues of pigs inoculated with respiratory or enteric strains of coronavirus to immunity against enteric coronavirus challenge.

Abstract: Two antigenically related porcine coronaviruses, transmissible gastroenteritis virus (TGEV) which infects primarily the intestinal tract and causes severe diarrhea, and porcine respiratory coronavirus (PRCV) which infects the respiratory tract and causes subclinical or mild respiratory infections, presented a unique opportunity to study the interrelationship of gut-(GALT) and bronchus-associated lymphoid tissues (BALT) and their contribution to protective immunity against TGEV infection. Pigs were inoculated o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
10

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 0 publications
0
2
0
10
Order By: Relevance
“…Studies have revealed that once the plasmablast leave the lymphoid nodes, they reach the lamina propria of the different mucosal membrane, where they differentiate into plasmatic cells due stimulation of IL-5 and IL-6 secreted by Th2 cells (Strober W, 2005). In addition, memory cells B and specific IgG antibodies have been proposed to accumulate in the lamina propria from inductor sites, and this same accumulation plays an important role in the protection against pathogens (VanCott et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that once the plasmablast leave the lymphoid nodes, they reach the lamina propria of the different mucosal membrane, where they differentiate into plasmatic cells due stimulation of IL-5 and IL-6 secreted by Th2 cells (Strober W, 2005). In addition, memory cells B and specific IgG antibodies have been proposed to accumulate in the lamina propria from inductor sites, and this same accumulation plays an important role in the protection against pathogens (VanCott et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The Vero cells infected with PEDV and mock antigens were grown and fixed in 96-well plates as described previously for TGEV ASCs ( 26 , 42 , 43 ). The ELISPOT assay for the quantification of PEDV-specific ASCs was performed following previous protocols ( 23 , 37 , 38 ).…”
Section: Methodsmentioning
confidence: 99%
“…El aislamiento y purificación de las CMN se realizó siguiendo procedimientos previamente descritos por otros autores (31,142,146,154). Se siguieron protocolos diferentes para el procesado de las muestras de intestino (duodeno e íleon), para el bazo y los ganglios linfáticos mesentéricos y para la sangre.…”
Section: 6-extracción De Células Mononuclearesunclassified
“…Nuestros resultados coinciden con trabajos realizados para otros virus gastroentéricos, en los que se ha comprobado que con la utilización de cepas de virus adaptadas al cultivo celular y administradas por vía oral u oronasal, se consigue un cierto grado de protección frente al virus virulento, aunque siempre menor que el descrito cuando los animales eran inoculados inicialmente con ese virus (17,115,117,119,142,154).…”
Section: Lechones Inoculados Con El Virus Atenuadounclassified
See 1 more Smart Citation